Analysis of Risk Factors for Acute Myocardial Infarction - Arlindyo, Muhammad Vieraldo Berly; Faizin, Chamim; Noviasari, Nina Anggraeni; Setiawan, Muhammad Riza (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Cardiovascular disease is the most common cause of death in the world. One part of cardiovascular disease is acute myocardial infarction. There are risk factors that have the potential such as age, gender, genetics, hypertension, smoking, dyslipidemia, and diabetes mellitus. This study aims to analyse the risk factors associated with acute myocardial infarction. This study was conducted in October 2023, using an analytical observational study type and cross-sectional design. This study used medical record data from AMI patients from June 2022 - June 2023. The study sample was respondents diagnosed with acute myocardial infarction at ROEMANI Hospital taken through total sampling. Inclusion was 60 and exclusion was 14 respondents. Data analysis uses the chi-square The results showed that those who had a significant relationship with the incidence of acute myocardial infarction included hypertension (p = 0.001), diabetes mellitus (p = 0.022), smoking (p = 0.045), and those who did not dyslipidemia (p=0.639). In conclusion, there is a significant relationship between hypertension, diabetes mellitus, and the incidence of acute myocardial infarction. At the same time, dyslipidemia does not have a significant relationship with the incidence of acute myocardial infarction.